Molecular characterization of microbial communities in aquaculture - Martins, Patrícia Tavares (2018)
Microorganisms play key roles in fish production and in the maintenance of fish health in aquaculture systems. However, there is still a lack of fundamental knowledge regarding the bacterial composition and diversity of these systems. The general goal of this study is to gain fundamental knowledge on the bacterial communities of different aquaculture systems using molecular techniques. Furthermore, we evaluate the use of molecular methodologies to detect potential fish pathogens and develop a new molecular approach for early detection of a fish pathogen (Photobacterium damselae) in aquaculture systems. In the intensive aquaculture, we assessed the composition of bacterial communities inhabiting recirculating aquaculture systems (RAS) of turbot (Scophthalmus maximus) and sole (Solea solea). Both molecular approaches, DGGE profiles and barcoded-pyrosequencing of 16S rRNA gene fragments, revealed differences between the bacterial communities of both RAS, suggesting that the fish species being cultured promoted a strong effect on water bacterial communities. Several potential pathogenic species were detected, however despite the presence of these pathogens, no symptomatic fish were observed during the study. In this study barcoded pyrosequencing showed to be an unprecedented technique for assessing bacterial communities and reveal potential pathogens. In the second phase of this study, we investigated seasonal patterns of bacterioplankton (free-living and particleassociated bacteria) composition and their putative function in a semi-intensive European seabass (Dicentrarchus labrax) aquaculture system located at Ria de Aveiro. The results indicated that shifts in the bacterioplankton communities are driven by seasonal changes of abiotic characteristics of the estuarine water. Furthermore, the use of bioinformatics tools such as PICRUSt to predict metagenome functional content allowed us a better understanding of microbial quality in this aquaculture system. Given the impact of disease outbreaks in the development of aquaculture sector, we developed a new molecular approach for fast detection of Photobacterium damselae subspecies, responsible for major economic losses in the aquaculture systems in Mediterranean countries of Europe. Specific primers targeting the toxR gene were designed for overall quantification of P. damselae species and specific detection of its subspecies (P. damselae piscicida and P. damselae damselae) based on real time PCR (RT-PCR) and PCR denaturing gradient gel electrophoresis (PCR-DGGE), respectively. This approach showed good specificity for quantification and detection of P. damselae subspecies in estuarine and aquaculture water samples. The molecular approach developed here can contribute for a more effective long-term management of fish health in aquaculture systems.